2014
DOI: 10.1016/j.tourman.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of international tourism demand forecasting and implications for practice

Abstract: :Numerous studies on tourism forecasting have now been published over the past five decades. However, no consensus has been reached in terms of which types of forecasting models tend to be more accurate and in which circumstances. This study uses meta-analysis to examine the relationships between the accuracy of different forecasting models, and the data characteristics and study features. By reviewing 65 studies published during the period 1980-2011, the meta-regression analysis shows that the origins of tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(185 citation statements)
references
References 118 publications
5
168
2
5
Order By: Relevance
“…Such result contrasts with the literature review by Peng et al (2014), where only fourteen papers from the total of 2,584 were found for Africa. Table 9 exhibits the modeling techniques adopted for the fifty articles considered.…”
Section: Resultscontrasting
confidence: 82%
See 2 more Smart Citations
“…Such result contrasts with the literature review by Peng et al (2014), where only fourteen papers from the total of 2,584 were found for Africa. Table 9 exhibits the modeling techniques adopted for the fifty articles considered.…”
Section: Resultscontrasting
confidence: 82%
“…However, artificial intelligence techniques such as neural networks (used for thirteen times) and support vector machines (adopted six times) appear now as the second dominant method, as opposed to the review from Peng et al (2014); such finding reveals a shift in the most recent years (i.e., after 2013) as opposed to the period before 2011, analyzed the paper of Peng et al (2014), in which only around 17% adopted these advanced artificial intelligence techniques. Also, the percentage weight of the econometrics-based methods (e.g., Markov regime-switching model) has decreased, when compared to the cited study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a growing interest in analyzing and forecasting tourism demand (Zhou-Grundy and Turner, 2014;Witt and Witt, 1995;Claveria and Torra, 2014;Peng et al, 2014). Researchers have used different quantitative methods for forecasting tourism demand.…”
Section: Introductionmentioning
confidence: 99%
“…See Song, Dwyer, Li and Cao (2012) and Peng, Song, and Crouch (2014) for a thorough review of tourism economics research and tourism demand forecasting studies. Nevertheless, the need for more accurate forecasts has led to an increasing use of AI techniques, such as fuzzy time series models and support vector machines (SVMs), or a mix of them (Pai, Hung, & Lin 2014;Cang & Yu 2014), in order to obtain more refined predictions of tourist arrivals at the destination level.…”
Section: Tourism Demand Forecasting With Ai-based Techniquesmentioning
confidence: 99%